Evaluation of analgesics use and misuse by Iraqi patients in Baghdad community - Mohammed, Samer I (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Analgesics which currently represent the corner stone of pain treatment are one of the most widely used and abused medications all over the â€Žworld â€Ž. Since analgesics used and misused widely in Iraqi community, the possibility of complications and adverse effect development from analgesics may be significant. The purpose of this study is to assess the attitude and degree of awareness about the correct use, side effects and complication of improper use of analgesics in Baghdad communityâ€Ž and to find if there is any correlation between the miss use of analgesic and the need to extra medication or treatment as a result of analgesic adverse effect. Method: This study was a cross-sectional survey using a pre-tested self-administered questionnaire which carried out in the different community pharmacy in Baghdad .An â€Ž11-question â€Ž questionnaire collect demographical information and attitudes to use analgesics by respondents. Results: Analgesics consumption increase with age. The majority of users, 46% reported taking analgesics for unspecified general body pain, followed by headache and other types of pain. (50.26%) of participant use analgesics frequently (more than 3 times weekly) and (57.44%) of them prefer certain type of analgesics and used it frequently. Larger percentage of analgesics recommended to Iraqi patients by a pharmacists, followed by a doctors or sometimes according to advice from a relative friend while only (18.46 %) were prescribed by patients themselves. Interestingly, (52.82%) of respondents have no information about the side â€Žeffectâ€Ž and higher percentage of them (61%) do not adhere to doses prescribed.â€Ž About (11.28 %) of respondents need for hospitalization â€Ž, (58%) consult a physician, andÂ (56%) use another medicines â€Ž as a result of side effects or complications of analgesics. Significant correlation confirmed between misuse of analgesics and the need for hospitalization and patients need for another medicine to treat side effects or complications of analgesics. Conclusion: Analgesics â€Ž consumed widely and most of the times incorrectly by Iraqi people in Baghdad and its usage usually associated with many complications as a result of a misuse by the patients due to improper dispensing information or education provided by pharmacist or other health care providers about the correct use or side effects associated with these medications.